2020
DOI: 10.21037/tlcr-20-1070
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the potential of circulating tumor DNA methylation patterns as prognostic biomarkers for lung squamous cell carcinoma

Abstract: Background: Aberrant epigenetic modifications play a key role in lung tumorigenesis. In our study, we aimed to explore the clinical implications of baseline circulating tumor DNA (ctDNA) somatic and methylation profiles in patients with lung squamous cell carcinoma (LUSC).Methods: A total of 26 patients with LUSC of various stages were included in this study. Somatic mutations and methylation levels were profiled from the plasma-derived ctDNA obtained at the time of diagnosis using unique molecular identifier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The whole-genome bisulfite sequencing library was generated by the brELSA method (Burning Rock Biotech, Guangzhou, China) ( 13 , 14 ). Briefly, purified cell-free DNA (cfDNA) was incubated with sodium bisulfite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole-genome bisulfite sequencing library was generated by the brELSA method (Burning Rock Biotech, Guangzhou, China) ( 13 , 14 ). Briefly, purified cell-free DNA (cfDNA) was incubated with sodium bisulfite.…”
Section: Methodsmentioning
confidence: 99%
“…Methylation levels were defined as scores to reflect the methylation features of each sample ( 13 , 14 ). The genomic region between the neighboring CpG sites with the r 2 value was defined as the methylation block.…”
Section: Methodsmentioning
confidence: 99%
“…Lung squamous cell carcinoma (LUSC), one of the major subtypes of NSCLC, accounts for nearly 30% of all confirmed cases of NSCLC, with the characteristics of rapid growth, quick metastasis and high mortality 2 . Although relatively sensitive to chemotherapy and radiotherapy, the 5-year survival rate for patients with LUSC is merely about 18% 3 . Platinum-based systemic chemotherapy is still the standard treatment for LUSC patients, but it often leads to clinical treatment failure due to the development of secondary chemoresistance 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of gene promoter regions is often linked to transcriptional silencing, while methylation of gene bodies has the opposite effect. Epigenetic dysregulation has been linked to the early stages of oncogenic transformation in a variety of solid tumors, and it can be used as a biomarker for early detection, systemic sampling, and prognosis in a variety of human cancers ( 13 ). Indeed, Haijing Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of gene promoter regions is often linked to transcriptional silencing, while methylation of gene bodies has the opposite effect. Epigenetic dysregulation has been linked to the early stages of oncogenic transformation in a variety of solid tumors, and it can be used as a biomarker for early detection, systemic sampling, and prognosis in a variety of human cancers (13). Indeed, Haijing Liu et al (14) reported the potential link between EGFR alterations at the multi-omics levels and clinical prognosis by pan-cancer analysis, but the relationship between DNA methylation of EGFR in LUAD and immune infiltration has not been reported.…”
Section: Introductionmentioning
confidence: 99%